Limiting Secularism : The Ethics of Coexistence in Indian Literature and Film - Kumar, Priya (Book collections on Project MUSE., 2008)
With a backdrop of religious violence and escalating regional tensions in South Asia, Priya Kumars Limiting Secularism probes the urgent topic of secularism and tolerance in Indian culture and life. Kumar explores Partition as the founding trauma of the Indian nation-state and traces the consequences of its marking off of Indian" from "Pakistani" and the positioning of Indian Muslims as strangers within the nation. Kumar unpacks the implications of the Nehruvian doctrine of tolerance-with all of its resonances of condescension and inequality-and asks whether more ethical cohabita